Examining the Influence of Family Support on Academic Achievement Among Home Economics Education Students - Sarifa Ainun; Sita Nurmasitah (Universitas Negeri Semarang, 2026)
The quality of higher education is frequently measured by student performance, a factor shaped by psychological and environmental conditions, with family support serving as a crucial microsystem under developmental ecology and Self-Determination Theory. This investigation examines the connection between familial assistance and the academic success of active learners in the Home Economics Education Study Program (PKK) at Universitas Negeri Semarang. Adopting a quantitative case study design, the research involved 65 students selected through non-probability sampling using the Slovin formula (e = 10%). Data were gathered via a 4-point Likert scale questionnaire assessing emotional, instrumental, motivational support, and family involvement, alongside Grade Point Average (GPA) records. Descriptive analysis and the Pearson Chi-Square test were employed to evaluate the relationship between variables. Findings indicate that 96.6% of students reporting high family support achieved high academic performance. Statistical evidence confirms a significant link (χ² = 30.039; df = 1; p < 0.001), validating family support as a protective factor for academic achievement. Theoretically, this work expands the discourse on social determinants within collectivist cultures. Practically, the insights offer a basis for developing academic guidance policies, strengthening family engagement, and improving counseling services that are more responsive to students’ conditions.